Dormancy and Revitalization: The fate of ethnobotanical knowledge of camel forage among Sahrawi nomads and refugees of Western Sahara - Volpato, Gabriele; Puri, Rajindra K. (Ethnobotany Research and Applications, 2014)
Knowledge about forage is fundamental to the survival of pastoral populations around the world. In this paper, we address the knowledge of camel forage of Sahrawi nomads and refugees of Western Sahara. We analyze the distribution of this knowledge through cultural consensus analysis and develop an explanation for intra-cultural variation based on changing processes of knowledge transmission. In total, 100 plant species were free-listed by informants, with five species (i.e., Acacia tortilis (Forssk.) Hayne, Nucularia perrinii Batt., Astragalus vogelii (Webb) Bornm., Panicum turgidum Forssk., and Stipagrostis plumosa Munro ex T.Anderson) found to be culturally highly salient. These five represent five local categories of forage that are necessary for camel management in the Western Sahara desert. The Sahrawi listed 25 forage plants that influence the taste and properties of camel milk, demonstrating that cultural values, as much as survival functions, underpin local knowledge systems. Perhaps unsurprisingly, age and nomadic experience are positively correlated with forage knowledge. Forced displacement and sedentarization are hypothesized as causes of progressive non-use of this knowledge and the lack of its transmission to younger generations of refugees. Nonetheless, across the study area, refugees are re-engaging with pastoralism and nomadism, which is leading to a revitalization of forage knowledge and its transmission. This should be regarded as an adaptation pathway for refugees. Para las poblaciones pastorales de todo el mundo, el conocimiento de las plantas forrajeras es fundamental para su supervivencia. En este trabajo se aborda el conocimiento sobre forraje de camellos entre los nómadas y los refugiados saharauis del Sáhara Occidental. Se analiza también la distribución de estos conocimientos a través de un análisis de consenso cultural, y se desarrolla una explicación para la variación intra-cultural basada en el cambio de los procesos de transmisión de conocimientos entre los refugiados. En total, 100 especies de plantas fueron enumeradas por los informantes, con cinco especies (Acacia tortilis (Forssk.) Hayne, Nucularia perrinii Batt., Astragalus vogelii (Webb) Bornm., Panicum turgidum Forssk., and Stipagrostis plumosa Munro ex T.Anderson) culturalmente muy relevantes. Las plantas forrajeras se clasifican en cinco categorías que son necesarias para la gestión de camellos en el desierto del Sahara occidental. Los saharauis reconocen 25 plantas forrajeras que influyen en el sabor y las propiedades de la leche de camella, hecho que muestra cómo los valores culturales, tanto como las funciones de supervivencia, sustentan los sistemas de conocimientos locales. Tal como era de esperar, la edad y la experiencia nómada están correlacionadas con el conocimiento de plantas forrajeras. El desplazamiento y la sedentarización forzada parecen ser la causa de la progresiva falta de utilización y transmisión de estos conocimientos a las generaciones más jóvenes de los refugiados. Sin embargo, dentro de un proceso más amplio de re-pastoralización de los refugiados, estos conocimientos están siendo reactivados y otra vez transmitidos a través de un proceso de revitalización que debe considerarse como una vía de adaptación de los refugiados. وفي هذه الورقة، سوف نتناول المعرفة بأعلاف الإبل بين الصحراويين واللاجئين من الصحراء الغربية. حيث سوف نقوم بتحليل توزيع هذه المعرفة من خلال تحليل الآراء الثقافية، ومن ثم وضع التفسير المناسب للتباين فيما بين تلك الثقافات على أساس التغيرات التي تطرأ على عمليات انتقال المعرفة. وبشكل عام، فقد تم إدراج 100 نبتة من قبل الخبراء في هذا المجال ومنها خمسة أنواع تبين أنها بارزة ثقافيا إلى حد كبير، وهي: Acacia tortilis (Forssk.) Hayne، Nucularia perrinii Batt.، Astragalus vogelii (Webb) Bornm.، Panicum turgidum Forssk.، Stipagrostis plumosa Munro ex T.Anderson. هذه الأنواع الخمسة تمثل خمس فئات من الأعلاف المحلية الضرورية لإدارة الإبل في الصحراء الغربية. ولقد ذكر الصحراويون 25 من النباتات العلفية التي تؤثر على طعم وخصائص حليب الإبل، مما يدل على أن القيم الثقافية، بقدر وظائف البقاء على قيد الحياة، هي من دعائم أنظمة المعرفة المحلية. ومما لا يثير الدهشة ربما، فإن السن والخبرة لدى البدو ترتبط بشكل إيجابي ومباشر مع المعرفة الأعلاف. وتفترض الورقة أن التهجير القسري والتوطين هي أسباب تفاقم عدم استخدام هذه المعرفة وعدم انتقالها إلى الأجيال الشابة من اللاجئين. وعلى الرغم من ذلك، فقد تم التحقق ف يالمنطقو قيد الدراسة من أن اللاجئين قد بدأوا بإعادة الانخراط مع الرعي والبداوة، وهو الأمر الذي يقود إلى تنشيط المعرفة بالأعلاف وانتقالها عبر الأجيال. وهو الأمر الذي ينبغي اعتباره بمثابة مسار تكيف للاجئين.